Strategi Coping Lansia dalam Menyesuaikan Diri di Panti Werda Pengayoman Kota Semarang - Hana Ishmah Khoirunnisa; Shalsabela Saputri; Abhista Evandhika Aulia; Ainaya Al Fatimah; Dhea Sintamaharani; Imam Aqil Macca Safrin Lalaki; Efna Nur Aisyah; Nailun Ni'mah Mahij; Gading Gumilang; Siti Hikmah (Lembaga Pengembangan Kinerja Dosen, 2025)
Elderly people living in nursing homes face complex social and psychological challenges, such as loss of social roles, isolation, and emotional distress due to environmental changes. This study aims to explore the coping strategies used by the elderly in adjusting to living in Pengayoman Nursing Home in Semarang City. A descriptive qualitative approach was used with a purposive sampling technique of three elderly and one nursing home manager as participants. Data were collected through semi-structured interviews and analyzed using thematic methods. The results showed that the elderly applied various coping strategies, with the dominance of emotion-focused coping such as accepting responsibility, positive reappraisal, seeking social support, and self-control. Some participants also used problem-focused coping such as planful problem solving through routine and creative activities to reduce stress. The orphanage also played a role through the provision of daily activities, emotional support, and cooperation with family or professionals. These findings suggest that adaptive coping strategies and adequate environmental support are essential in supporting the adjustment process of the elderly in nursing homes.